Проблеми становлення екологічної політики в Україні як основного чинника формування екологічної культури сьогодення - Сулацкова, Ольга; Sulatskova, Olga (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано формування екологічної політики як обов’язкової умови для збалансованого розвитку України, розкрито питання економічних причин сучасної екологічної кризи. Зроблено висновок, що екологічна політика є важливим чинником збереження умов існування людини, а екологічна культура дедалі більше утверджується в суспільній свідомості як компонент стійкого розвитку та пріоритет безпеки держави. В екологічній культурі картина світу постає у всьому різноманітті і раціонального, і духовного втілення. Саме тому вона покликана відігравати провідну роль у сучасних драматичних процесах національного відродження й державотворення. The article presents the analysis of the formation of environmental policy, as a necessary condition for the sustainable development of Ukraine, reveals the economic causes of the present ecological crisis. The accession of Ukraine to the global civilization process determines the need for full consideration of the interests of all strata of society in the process of state-building, improving the quality of life of the population, ensuring a dynamic and harmonious development of man, his spiritual life and intellectual qualities, and social justice. The study showed that the effectiveness of environmental activities primarily depends on the environmental policies implemented at the national and regional levels. The analysis shows that it has not become a necessary part of our life as it is declared in many documents, and does not meet the expectations of the society. It is concluded that the environmental policy is an important factor in maintaining the conditions of human existence and ecological culture more and more and more entrenched in the public consciousness as a component of sustainable development as the priority of the security of the state. In an ecological culture picture of the world presented in the diversity of both rational and spiritual realization. That is why it is called upon to play a leading role in modern drama processes of national revival and the creation of the state.
Problems of Formation of Environmental Policy in Ukraine, as the Main Factor in the Formation of Ecological Culture of Modernity
Keywords: екологія; ecology; культура; culture; екологічна політика; environmental policy; екологічна культура; environmental culture